The Role of Islamic Psychoeducation in Muslim Family Counseling in The Digital Era - Husna, Farisah Habibah (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The digital era brings both opportunities and risks for Muslim families. While technology facilitates access to Islamic knowledge, it also exposes families to harmful content, reduced emotional connection, and moral degradation. This conceptual study explores the role of Islamic Psychoeducation—a psychological educational approach integrated with Qur’anic and prophetic values—in strengthening Muslim family resilience amid digital challenges. Drawing upon the theoretical framework of Family Psychoeducation (FPE), Cognitive Behavioral Therapy (CBT), and Islamic Psychology, the article proposes a six-pillar model encompassing: (1) tauhidi meaning-making, (2) value-based digital literacy, (3) emotion regulation through tazkiyah al-nafs, (4) Qur’anic communication and problem solving, (5) family–school–mosque collaboration, and (6) gradual evaluation. This model aims to integrate evidence-based psychological practice with spiritual principles, offering a culturally and religiously congruent counseling framework. Further empirical validation through controlled trials is recommended to strengthen its scientific reliability and contextual applicability